Analisis Penggunaan Aplikasi Wordwall Pada Pembelajaran IPA Kelas IV di SD Negeri 249 Palembang - Sidik, Fajar (Journal of Innovation in Teaching and Instructional Media, 2024)
This study improved the learning outcomes of class IV students at SDN 249 Palembang by using the wordwall application in science subjects. This study used descriptive qualitative. The stages of data collection are observation and interviews. Data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The results of the research on wordwall learning media are one of the interactive media that is easy to use, and can increase student interest and motivation in learning science. Wordwall learning media can be used as one of the media in bold learning as it is today. In addition to being easy and inexpensive to use, this media also has many alternative choices in presenting material and questions. So that educators can use other alternative options as other variations in packaging other subject matter. Fun and varied media will make students more active and more interested in following the learning process boldly.